2015
DOI: 10.1093/humrep/dev203
|View full text |Cite
|
Sign up to set email alerts
|

Physical health of singleton children born after frozen embryo transfer using slow freezing: a 3-year follow-up study

Abstract: This study was funded by the University Hospital of Oulu and Helsinki, Finland. The National Institute for Health and Welfare (THL) covered the data linkages and the work of Mika Gissler. There are no competing interests to be reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Our results also indicated that freeze-thawing procedure, as well as ICSI, might increase the risks of immune dysfunction in offspring. Though the risks of hospital admission in FET-conceived children and asthma medication in ART-conceived children have been reported to be higher than CTRL conceived children 32,33 , direct evidence regarding the effects of ART on the immune system is lacking so far and long-term follow-up studies are required. Previous studies have revealed elevated rates of preeclampsia in women who have undergone FET 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicated that freeze-thawing procedure, as well as ICSI, might increase the risks of immune dysfunction in offspring. Though the risks of hospital admission in FET-conceived children and asthma medication in ART-conceived children have been reported to be higher than CTRL conceived children 32,33 , direct evidence regarding the effects of ART on the immune system is lacking so far and long-term follow-up studies are required. Previous studies have revealed elevated rates of preeclampsia in women who have undergone FET 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Embryo freezing can also be offered to single women with TS using donor sperm after counselling about the implications. Emerging data suggest similar pregnancy rates and better perinatal outcomes and health of children born through the use of frozen embryos compared to fresh IVF/ICSI treatment …”
Section: Routes To Parenthood For Women With Turner Syndromementioning
confidence: 99%
“…There is some evidence to suggest similar pregnancy rates and better perinatal outcomes and health of children born through the use of frozen embryos compared to the use of fresh IVF/ICSI treatment in the general infertile population . However, there is no good evidence on pregnancy outcomes for women with TS who undergo oocyte or embryo freezing.…”
Section: Routes To Parenthood For Women With Turner Syndromementioning
confidence: 99%
See 2 more Smart Citations